B3 Transcription Factors Determine Iron Distribution and FERRITIN Gene Expression in Embryo but Do Not Control Total Seed Iron Content - Grant-Grant, Susana; Schaffhauser, Macarena; Baeza-Gonzalez, Pablo; Gao, Fei; Conéjéro, Geneviève; Vidal, Elena A.; Gaymard, Frederic; Dubos, Christian; Curie, Catherine; Roschzttardtz, Hannetz (Frontiers in Plant Science, 2022)
Iron is an essential micronutrient for humans and other organisms. Its deficiency is one of the leading causes of anemia worldwide. The world health organization has proposed that an alternative to increasing iron content in food is through crop biofortification. One of the most consumed part of crops is the seed, however, little is known about how iron accumulation in seed occurs and how it is regulated. B3 transcription factors play a critical role in the accumulation of storage compounds such as proteins and lipids. Their role in seed maturation has been well characterized. However, their relevance in accumulation and distribution of micronutrients like iron remains unknown. In Arabidopsis thaliana and other plant models, three master regulators belonging to the B3 transcription factors family have been identified: FUSCA3 (FUS3), LEAFY COTYLEDON2 (LEC2), and ABSCISIC ACID INSENSITIVE 3 (ABI3). In this work, we studied how seed iron homeostasis is affected in B3 transcription factors mutants using histological and molecular approaches. We determined that iron distribution is modified in abi3, lec2, and fus3 embryo mutants. For abi3-6 and fus3-3 mutant embryos, iron was less accumulated in vacuoles of cells surrounding provasculature compared with wild type embryos. lec2-1 embryos showed no difference in the pattern of iron distribution in hypocotyl, but a dramatic decrease of iron was observed in cotyledons. Interestingly, for the three mutant genotypes, total iron content in dry mutant seeds showed no difference compared to wild type. At the molecular level, we showed that genes encoding the iron storage ferritins proteins are misregulated in mutant seeds. Altogether our results support a role of the B3 transcription factors ABI3, LEC2, and FUS3 in maintaining iron homeostasis in Arabidopsis embryos.